2009
DOI: 10.1590/s1806-37132009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Transporte intra-hospitalar de pacientes sob ventilação invasiva: repercussões cardiorrespiratórias e eventos adversos

Abstract: Objective: To determine the occurrence of cardiorespiratory alterations and to identify adverse events during the intrahospital transport of patients on invasive ventilation. Methods: A prospective observational non-randomized study was conducted at two tertiary hospitals between April of 2005 and December of 2006. We included patients on invasive ventilation who required intrahospital transport during the study period. Exclusion criteria were as follows: being under suspicion of brain death; being submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 27 publications
1
22
0
10
Order By: Relevance
“…One explanation is the different types of patients studied. Patients studied include those in the medical ICU [ 3 ], surgical ICU [ 7 ], anesthesiological ICU [ 6 ], neurological ICU [ 8 ], and emergency department [ 9 11 ]; mechanically ventilated patients [ 2 , 3 , 12 ]; and patients going to different transport destinations. Another explanation is the different definitions of AEs used among various reports.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation is the different types of patients studied. Patients studied include those in the medical ICU [ 3 ], surgical ICU [ 7 ], anesthesiological ICU [ 6 ], neurological ICU [ 8 ], and emergency department [ 9 11 ]; mechanically ventilated patients [ 2 , 3 , 12 ]; and patients going to different transport destinations. Another explanation is the different definitions of AEs used among various reports.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain the low impact found on PaCO 2 , pH, bicarbonate and base excess. A Brazilian study 6 showed that blood gas changes found during the transport of critically-ill intra-hospital patients display a pH with a tendency to alkalosis and a reduction of CO 2 . In this study, these data were not observed.The said study also reported that there is a tendency for a decrease in oxygenation during transport; this fact was also not evident.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…During this mode of transport, in most cases patients are hemodynamically stable. Zuchelo and Chiavone 6 and Gervais et al 7 reported that gasometries Gonsaga…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 98%
“…[ 27 ] Zuchelo and Chiavone explored alterations of arterial pH (a change in arterial pH was defined as pH change >0.07 during transport) in 58 IHT patients and found that 17% of patients met this criterion, 8 patients had increased pH while 2 had decreased pH values. [ 51 ] After examining PaCO 2 values, it was discovered that four patients had decreased PaCO 2, while one had increased PaCO 2 . These data suggest that IHT may result in non-trivial changes in pH and PaCO 2 with the associated potential for alterations in patient physiology.…”
Section: Acid/base Disordersmentioning
confidence: 99%
“…These data suggest that IHT may result in non-trivial changes in pH and PaCO 2 with the associated potential for alterations in patient physiology. [ 51 ]…”
Section: Acid/base Disordersmentioning
confidence: 99%